2016
DOI: 10.1097/qad.0000000000001072
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in the oral cavity of HIV patients is not reduced by initiating antiretroviral therapy

Abstract: Objective:The incidence of human papillomavirus (HPV)-related oral malignancies is increasing among HIV-infected populations, and the prevalence of oral warts has reportedly increased among HIV patients receiving antiretroviral therapy (ART). We explored whether ART initiation among treatment-naive HIV-positive adults is followed by a change in oral HPV infection or the occurrence of oral warts.Design:Prospective, observational study.Methods:HIV-1 infected, ART-naive adults initiating ART in a clinical trial w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 26 publications
6
39
1
1
Order By: Relevance
“…Despite our low rate of detection, we did find associations with low CD4 count and high VL similar to that reported in adults [2, 3, 5]. In a recent study of 388 treatment-naïve HIV-infected adults, men showed a higher rate of oral HPV than women (20% vs 11%, respectively, p=0.06) however, no difference was seen with respect to oral shedding of oncogenic HPV subgenotypes (4% and 5%, respectively) similar to our findings [14]. Another possible reason we observed low rates of HPV is that these sexually active HIV-infected youth entered puberty on ART with relatively well controlled HIV infection.…”
supporting
confidence: 91%
“…Despite our low rate of detection, we did find associations with low CD4 count and high VL similar to that reported in adults [2, 3, 5]. In a recent study of 388 treatment-naïve HIV-infected adults, men showed a higher rate of oral HPV than women (20% vs 11%, respectively, p=0.06) however, no difference was seen with respect to oral shedding of oncogenic HPV subgenotypes (4% and 5%, respectively) similar to our findings [14]. Another possible reason we observed low rates of HPV is that these sexually active HIV-infected youth entered puberty on ART with relatively well controlled HIV infection.…”
supporting
confidence: 91%
“…A recent clinical trial has investigated the effect of HIV in HPV infection in the presence and absence of combination antiretroviral therapy [41]. The levels of oral HPV DNA in the co-infected patients, which was monitored for 24 weeks after the start of cART, remained elevated throughout therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Equilibrium values for HIV RNA per ml and HIV-specific uninfected CD4+ T cells per ml were reported in an HIV/HPV co-infection study to be = 4.8x10 4 virions per ml and = 3.3x10 5 cells per ml [41]. Since the patient is in a chronic HIV steady state, we derive , β and s from steady state conditions , and , to be = 2.4x10 3 cells per ml, β = 1.5x10 -7 ml per cells per day and s = 5.6x10 3 cells per ml per day.…”
Section: Resultsmentioning
confidence: 99%
“…A5264 was a comparison of ART alone • To evaluate the effect of ART initiation on oral HPV shedding and occurrence of oral warts • To evaluate the association between the development of oral warts and (i) CD4+ T cell count changes; and (ii) plasma HIV-RNA load at 4-week, 16-week, and 24-week follow-ups after ART initiation Study completed. (Shiboski et al, 2015b; CROI and manuscript submitted) a AMC052 is a protocol of the AIDS Malignancy Consortium that is conducted in collaboration with the ACTG.…”
Section: Laboratory Activitymentioning
confidence: 99%
“…Among the protocols that focused on HPV, protocol A5272 sought to explore whether ART initiation among treatment-na€ ıve HIV-positive adults was followed by an increase in oral wart incidence or a decrease in oral HPV shedding (Shiboski et al, 2015b). The rationale for this work was that previous studies have suggested an increase in the incidence of oral warts following antiretroviral therapy (ART) initiation.…”
Section: à3mentioning
confidence: 99%